Penerapan Metode Zillmer dan Illinois Pada Perhitungan Cadangan Premi Asuransi Jiwa Joint Life - Chandra, Veronica Celine; Widana, I Nyoman; Wijayakusuma, IGN Lanang (Publisher : Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Joint life insurance is life insurance whose premium payments end at the first death of one of the insureds. This study aims to calculate the value of premium reserves using the Zillmer and Illinois methods for two insureds with data obtained from PT. Allianz where the insured is 33 and 29 years old with a protection period of 15 years, a premium payment period of 10 years. The Zillmer method uses prospective calculations as a basis for calculations that do not depend on the term of the product used, while the Illinois method is part of the prospective method by limiting costs charged to insurance participants with a limit of 20 years of payment. The results of this study are the value of premiums and premium reserves using the Zillmer and Illinois methods in this study are greater than the value of premiums and premium reserves from PT. Allianz. In the first year, the premium reserve value for the Zillmer method is IDR 80.005.964 while for the Illinois method is IDR 62.902.458 where the reserve value for the following year always increases with the reserve value for the Zillmer method being greater than the Illinois method. The premium reserves for the Zillmer and Illinois methods at the end of the year have the same value as the compensation value of IDR 1.130.000.000, which means that the insurance company is ready to provide compensation as much as promised to insurance participants.